Locking Plate Fixation for Intra-Articular Fractures of Calcaneum - Salunke, Abhijeet A; Vachalam, Danakrishna; Menon, Prem H; S Saseendar; Tan Junha; Singh, Gurpal (International Journal of Medical Research, 2014)
Surgical management of calcaneum fracture consists of open reduction with proper reduction of intra-articular fragments and fixation with plating. Locking plate systems have been used for fixation of intra-articular fractures. The locking plate fixation provides a simple and adequate fixation for management of displaced intra-articular calcaneal fractures. The open reduction and internal fixation method with locking plates can be a rewarding technique for early mobilization and better fracture reduction in calcaneal fractures.